Epeorus petersi, a new species of Heptageniidae (Ephemeroptera) from the Western Ghats of southern India - Sivaruban, T.; Barathy, S.; Arunachalam, M.; Venkataraman, K.; Sivaramakrishnan, K. G. (Zootaxa, 2013)
Heptageniidae is a family of mayflies (Ephemeroptera) distributed mainly in the Holarctic, Oriental and Afrotropical regions (Webb & McCafferty 2008). This family is Laurasian in origin and is a conspicuous component of the benthic community in the hill streams of the Western Ghats of southern India. This is a global hotspot of biodiversity endowed with a high degree of species endemism and is considered a significant reservoir of ancient lineages (Bossuyt et al. 2005).